Dampak Wisata Bahari Bagi Kondisi Ekonomi Masyarakat Desa Kolorai, Kecamatan Morotai Selatan, Kabupaten Pulau Morotai - Muhamad Adhiyaksa; Annisa Mu'awanah Sukmawati (Uniplan: Journal of Urban and Regional Planning, 2021)
Kolorai Village has a variety of tourism potentials, they are cultural tourism, nature tourism, and marine tourism. Marine tourism is a type of tourism that has become the mainstay of Kolorai Village and has the opportunity to have a positive impact on the economic development of coastal communities. The research is located in Kolorai Village, South Morotai District, Morotai Island Regency. This study aims to analyze the impact of marine tourism on the economic conditions of the local people in Kolorai Village, South Morotai District, Morotai Island Regency. The research method conducted by using a quantitative method with Crosstab analysis techniques to exam the correlation between the existence of marine tourism and changes in income levels. Data collection was carried out by collecting primary data through questionnaires, interviews, and field observations as well as secondary data collection from document review. The results showed that the presence of marine tourism in Kolorai Village had a significant impact on the economy of the local community. This can be seen from the existence of new livelihood opportunities for local people who are not only as fishermen but also as marine tourism business actors and tourism accommodation service providers. The existence of accessibility and diversification of tourist attractions also affects the dynamics of community income in the marine tourism sector.